Status pengelolaan minyak jelantah di Kota Salatiga dan identifikasi faktor-faktor yang mempengaruhinya - Juniabela, Salomita Rahma; Oktaviana, Shalva Dilla; Agatha, Claudia; Dewi, Citra Anisya; Handayani, Widhi (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
Cooking oil is one of the basic needs used by all levels of society. Repeated use of cooking oil can turn it into waste cooking oil which can be bad for health. Disposal of waste cooking oil into the environment has a negative impact on the environment, so it should be managed properly. This study was conducted to explain the management of waste cooking oil in Salatiga City and identify the factors that influence the quality of waste cooking oil management. This qualitative research uses a case study involving 12 informants. The results showed that informants usually used packaged cooking oil repeatedly. The behavior of informants often throws used cooking oil, although some collected it and sold it to collectors. They know the risks of using used cooking oil on health, but education to increase their knowledge regarding the negative impact of waste cooking oil on the environment is still needed. Public knowledge and awareness, the availability of infrastructure, regulations, and the reliability of the waste cooking oil management system, are some of the key factors needed to improve the quality of used used cooking oil in Salatiga City.